Logistics of International Express Shipping and Air Traffic - Pašagić Škrinjar, Jasmina; Drljača, Miroslav; Kavran, Zvonko (Promet - Traffic&Transportation, 2013)
The paper studies the relations between logistics of international express shipments and air traffic analysing the basic characteristics of international express shipments that are carried by combined transport, usually road vehicles and aircraft. The paper indicates the possibility of optimising individual technological processes in the logistic chain of express shipments distribution. It analyses the forms for the calculation of time slots in single logistic chain hubs of collecting and delivery of express shipments. It has been shown that the international distribution chains in the air express sector, related to the globalisation process, change the traditional functions of combined ground-air transport. Here, the increased investment into automation plays the crucial role in the development strategies of companies and in the operationalization of the quality policy of numerous carriers of express shipments by air.